Literary Journalism dan Perkembangannya di Indonesia - R. Masri Sareb Putra (Universitas Multimedia Nusantara, 2010)
The new journalism or literary journalism is the new genre in the world of journalism. It is considered ‘new' because it is the hybrid of conventional journalism which takes the shape of inverted pyramid and uses the style of literature which applies literary elements and regulations. The elements and the literary style in this type of journalism can be strongly perceived. Thus, it is named ‘literary journalism'. This type of journalism has long been introduced to the United States of America by literary-journalist such as John Hersey, Tom Wolf, Norman Mailer, or Gay Talese. In Indonesia literary journalism began as early as when Tempo magazine supported by a number literary-journalist commenced to apply the narrative journalism. Kata Kunci: Literary journalism, jurnalistik sastrawi, jurnalistik, sastra, cerita, hibrida